Children's journalism and child character building - Al-Hindawi, Fawzi Hadi; Al-Milaji, Suhad Mahmoud Majah (Al-Adab Journal, 2021)
Children's journalism occupies a large and important place in educating children and shaping their personalities and it is among the great cultural factors, because it contributes to guidance, information, education, entertainment, development of taste, formation of customs and traditions, and the transfer of values, principles and ideas to children.Children’s journalism uses science, literature and arts and chooses what is appropriate with the perceptions of children to convey it after simplifying it to children, reinforced with pictures and drawings, and this cultivates their love of reading, develops their language, expands their information, and stimulates their imagination.Children's literature transmits through the press a set of moral, social, human, scientific and national values, and instills them in children.